The nutritional interrelationship between the growing and finishing phases in crossbred cattle raised in a tropical system - Sampaio, Ricardo Linhares; de Resende, Flávio Dutra [UNESP]; Reis, Ricardo Andrade [UNESP]; de Oliveira, Ivanna Moraes; Custódio, Letícia [UNESP]; Fernandes, Rodolfo Maciel [UNESP]; Pazdiora, Raul Dirceu; Siqueira, Gustavo Rezende [UNESP] (Springer Nature, 2017)
This study evaluated the nutritional interrelationship between the growing and finishing phases of crossbred cattle in determining their performance. One hundred and eight animals were used (8 months old, body weight [BW] 211 ± 20 kg). During the dry season, the animals received one of the following supplements: a mineral plus urea supplement (ad libitum, MSD), a protein supplement (1 g/kg BW per day, PR1), or a protein-energy supplement (5 g/kg BW per day, PE). During the rainy season, the animals received one of the following supplements: a mineral without urea supplement (ad libitum, MSR), a protein supplement (1 g/kg BW per day, PR2), or PE (5 g/kg BW per day). The experimental design was completely randomized using a 3 × 3 factorial scheme (for the rainy season) and a 3 × 3 × 2 factorial scheme (for the finishing phase). The supplementation and finishing systems were considered to be the treatments, and the animals were considered to be the experimental units. Dry season supplementation did not affect the average daily gain (ADG) during the rainy season (P = 0.12) or the finishing phase (P = 0.73). An increase in the level of rainy season supplementation reduced ADG by 12% during the finishing phase (P < 0.06). Providing PE during the dry and rainy seasons led to the animals being slaughtered 17 (P = 0.06) and 30 (P < 0.01) days earlier, respectively. Our results indicate that supplementation during the dry season (under poor-quality pasture conditions) does not affect the performance during the rainy season or the finishing phase. Furthermore, while providing PE during the rainy season can reduce ADG during finishing, the higher BW at the beginning of the finishing phase is sufficient to reduce the time of the finishing period.
Keywords: Body composition; Carcass; Intact male; Marandu grass